Policy Consequences of Multiple Equilibria and the Indeterminacy of Economic Outcomes in a Boundedly Rational World: Closing the System with Non-Economic Variables1. Issue 3 (3rd July 2017) - Altman, Morris
Abstract: In the conventional economic wisdom, the notion of unique equilibria that are efficient and Pareto optimal dominates the modeling discourse. Hebert Simon proposed an alternative analytical framework where the notion of multiple and sustainable equilibria is critical. Multiple equilibrium is the crucial stylized fact of economic life that requires better understanding and modeling. Of particular significance, Simon touched on the importance of institutions and differential power relationships in affecting economic outcomes. But this modeling approach was not well developed by Simon. Following from his contributions, further develop the notion of multiple equilibria especially in the realm of production with an emphasis on x-efficiency theory. I bring to bear the importance of institutional parameters (including power relationships), culture, norms, ethics, and moral sentiments to the determination of economic outcomes. In the model developed here, boundedly rational decision-makers' choices are contextualized and constrained by complex environmental factors. No one choice is either inevitable or economically efficient. A multiplicity of outcomes is possible and sustainable inclusive of those that are suboptimal. Much depends on individual preferences and institutional design. This has significant implication for institutional design and policy.